Newton based homotopy optimization method for solving global optimization problem - Ahmad Zharif Salami Mohd Taha, 1985-; Ismail Kamis, supervisor; Fakulti Sains (2013)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2013